Optimal irrigation and fertilizer amounts based on multi-level fuzzy comprehensive evaluation of yield, growth and fruit quality on cherry tomato - He, Zhihao; Li, Manning; Cai, Zelin; Zhao, Rongsheng; Hong, Tingting; Yang, Zhi; Zhang, Zhi (Agricultural water management, 2021)
•Water-fertilizer coupling model was established based on the integrated growth.•Irrigation mainly affected the integrated growth of cherry tomato in 2018S.•Irrigation and N mainly affected the integrated growth of cherry tomato in 2018F.•The optimal strategy of water and fertilizer were determined in two seasons. The accurate and efficient management of irrigation and fertilizer is essential for the effective intensive production of greenhouse cherry tomato. In this study, we evaluated the effects of irrigation and fertilizer combinations on yield, growth, and nutritional and taste quality of cherry tomato. More specifically, we applied a quadratic orthogonal rotation combination design with four experimental factors at five levels (-1.68, -1, 0, 1, 1.68) for a total of 23 treatments over two consecutive growing seasons in 2018. A multi-level fuzzy comprehensive evaluation (MFCE) was constructed, including four factors and 14 subfactors, as well as a water and fertilizer multi-factor regulation model for the integrated growth of cherry tomato. Single experimental factor effects included irrigation in the spring season (2018S), with the other experimental factors following a downward opening parabola with integrated cherry tomato growth for both seasons. The integrated growth increased with irrigation, and exhibited a rise and subsequent fall with phosphate (P2O5) and potash (K2O) in 2018S, as well as with irrigation and nitrogen (N) levels in the fall season (2018 F). The experimental factor interaction values of 1.68 for irrigation (1978.0 m3/ha), 0.94 for N (482.2 kg/ha), -0.69 for P2O5 (104.4 kg/ha) and -0.65 for K2O (181.3 kg/ha) were observed to be optimal for the integrated growth of cherry tomato in 2018S. The corresponding combination for 2018 F was determined as 0.70 for irrigation (1082.9 m3/ha), 0.51 for N (287.9 kg/ha), 0 for P2O5 (126.5 kg/ha) and -0.41 for K2O (159.7 kg/ha). Furthermore, the irrigation, N, P2O5, and K2O intervals that maximized cherry tomato growth over the two seasons were as follows: i) 1780.2–1978.0 m3/ha, 434.0–482.2 kg/ha, 94.0–104.4 kg/ha, and 163.2–181.3 kg/ha for 2018S; and 974.6–1082.9 m3/ha, 259.1–287.9 kg/ha, 113.9–126.5 kg/ha and 143.7–159.7 kg/ha for 2018 F, respectively. Comprehensively understanding the growth of cherry tomato can potentially enhance cherry tomato production in the arid regions of northwestern China.